Experimental investigation of exercise-related hedonic responses to preferred and imposed media content - Emily Frith; Paul D. Loprinzi (Tabriz University of Medical Sciences, 2018)
Background: We evaluated the differential influence of preferred versus imposed media selections on distinct hedonic responses to an acute bout of treadmill walking. Methods: Twenty university students were recruited for this [160 person-visit] laboratory experiment, which employed a within-subject, counter-balanced design. Participants were exposed to 8 experimental conditions, including (1) Exercise Only, (2) Texting Only, (3) Preferred Phone Call, (4) Imposed Phone Call, (5) Preferred Music Playlist, (6) Imposed Music Playlist, (7)Preferred Video and (8) Imposed Video. During each visit (except Texting Only), participants completed a 10-minute bout of walking on the treadmill at a self-selected pace. Walking speed was identical for all experimental conditions. Before, at the midpoint of exercise, and post-exercise, participants completed the Feeling Scale (FS) and the Felt Arousal Scale (FAS) to measure acute hedonic response. The Affective Circumplex Scale was administered pre-exercise and post-exercise.Results: Significant pre-post change scores were observed for happy (Imposed Call: P=0.05;Preferred Music: P=0.02; Imposed Video: P=0.03), excited (Exercise Only: P=0.001; PreferredVideo: P=0.01; Imposed Video: P=0.03), sad (Preferred Music: P=0.05), anxious (ExerciseOnly: P=0.05; Preferred Video: P=0.01), and fatigue (Exercise Only: P=0.03; Imposed Video:P=0.002). For the FS all change scores were statistically significant from pre-to-mid and pre-topost (P<0.05).Conclusion: This experiment provides strong evidence that entertaining media platforms substantively influences hedonic responses to exercise. Implications of these findings are discussed.